Views about perceived training needs of health care professionals in relation to socially assistive robots: an international online survey - Papadopoulos, Irena; Koulouglioti, Christina; Lazzarino, Runa; Ali, Sheila; Wright, Steve; Martín-García, Ángel; Oter-Quintana, Cristina; Kouta, Christiana; Rousou, Elena; Papp, Katalin; Krepinska, Radka; Tóthová, Valerie; et al. (My University, 2023)
As Artificial Intelligence and social robots are increasingly used in health and social care, it is imperative to explore the training needs of the workforce, factoring in their cultural background.
Keywords: country culture; international study; midwives; nurses; social care professionals; socially assistive robots; training needs